Indonesian Women’s Experiences in Dealing with the Impacts of Pandemic Covid-19 - Alimatul Qibtiyah (Yayasan Jurnal Perempuan, 2020)
The Covid-19 pandemic has had a very serious impact, because it is very massive, which has occurred in almost all countries and at all levels and groups of society. Disasters have a strong social dimension, especially in relation to vulnerability which often intersects with existing social stratification. In various disasters, women are among the groups most vulnerable to being affected, especially if the patriarchal culture is still strong and intertwined with misogynistic interpretations of religion and an economic and political system that is not friendly to women. This paper looks at the extent of the impacts of this pandemic on women, and how state regulations exist to deal with these impacts, as well as what efforts are being made by women both individually and in groups. This research was conducted by collecting documentation from various research results that have been conducted by several institutions, observation and interviews with several women at various levels and backgrounds. The results of this study indicate that women are the most vulnerable group and most affected by the Covid-19 Pandemic. Although it was a bit late, the government involved women in decision-making with a special mandate, regarding the handling of women, children and vulnerable groups. Women's experiences both individually and colletively through organizations in respond to this pandemic deserve paresiasi. Women in a pandemic situation have uniqueness in dealing with a pandemic in a more creative, resilient manner and also implementing a sisterhood.